Cooling-controlled and reliable driving module for low-level light therapy LED helmet. (November 2017) - Wang, Pengbo; Sun, Jiajing; Jiang, Qian; Li, Ting
Abstract: Stroke is a horrible disease of high incidence, which is the second leading cause of disability worldwide. Thousands of people are suffering from stroke sequelae. Therefore, how to rehabilitate from stroke sequela is an urgent research field benefiting human beings. The traditional and experience-based treatment methods not only have an uncertain treatment effect, but were also unsuitable to be widely used due to its unstable therapeutic effect. Transcranial low level light/laser therapy (LLLT) of neurological diseases and brain trauma has gained momentum due to the character of high-efficient, safe and non-invasive in the past decade. In this study, we developed a LLLT helmet with cooling-controlled and reliable driving module for treating stroke depending on near-infrared light. An application of integrated constant-current driving solution under high power is introduced in this paper. In order to reduce the large heat release of instrument and voltage drift of reference source, the major factors of current fluctuation, we proposed an integral thermal cooling solution and a multi-element parallel reference sources with temperature compensation to enhance the stability and robustness of the LLLT helmet. A series of experiments were performed to quantitatively testify the robustness and stability of our instrument. Highlights: Developed a LED-based low level light therapy helmet for treating brain dysfunction. Reliable, stable, and cooling-controlled driving module The effective control, cooling effect, and stability of the helmet are fully testified.